1993
DOI: 10.1002/jso.2930530525
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chemoembolization for hepatocellular carcinoma

Abstract: In a group of 396 patients who had chemoembolization for hepatocellular carcinoma (HCC) between 1984 and 1991, 67 underwent surgery (segmentaryhbsegmentary resections: 3 1 ; or transplantation: 36). Morbidity was limited to hepatic insufficiency (seven), arterial thrombosis (two), vasculitis (five), cholecystitis (two), and hepatic abscess (one). Perioperative mortality was 5.5% for transplantation and 6.7% for resection.Histological examination of resected specimens showed a total or subtotal tumor necrosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 10 publications
1
19
0
1
Order By: Relevance
“…10,11,[22][23][24][25] Early recurrence is generally correlated with understaging, 4,10,25-28 incomplete tumor excision, 11,[25][26][27][29][30][31][32] or multiple tumor cell dissemination inside or outside the liver through the portal venous system 33 during surgical manipulation of the tumorous livers. 4,13,34,35 Microscopic residual disease in the remaining liver can develop soon after LR, partly because resection itself leads to regeneration and is the most potent growth stimulus for liver-derived cells known to date. 26 Because the regeneration process is unable to affect the diseased parenchyma in a patient with cirrhosis, 36 a growth response can only be expected in the neoplastic hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11,[22][23][24][25] Early recurrence is generally correlated with understaging, 4,10,25-28 incomplete tumor excision, 11,[25][26][27][29][30][31][32] or multiple tumor cell dissemination inside or outside the liver through the portal venous system 33 during surgical manipulation of the tumorous livers. 4,13,34,35 Microscopic residual disease in the remaining liver can develop soon after LR, partly because resection itself leads to regeneration and is the most potent growth stimulus for liver-derived cells known to date. 26 Because the regeneration process is unable to affect the diseased parenchyma in a patient with cirrhosis, 36 a growth response can only be expected in the neoplastic hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This increases resectability, prevents cancer cell dissemination during surgery, sterilizes undetected lesions, and ultimately improves the survival rate. [12][13][14][15][16][17][18][19][20] The aim of our study is to clarify in a prospective trial whether preoperative TACE can reduce HCC recurrence after LR and improve disease-free and overall survival.…”
mentioning
confidence: 99%
“…AsĂ­, el estudio retrospectivo de Veltri et al 14 con controles histĂłricos mostraba una mejor supervivencia en los pacientes tratados con TACE, pero sĂłlo cuando se combinaba con IPE. Otros 5 estudios no controlados indicaban un cierto beneficio de la TACE realizada antes del TH [15][16][17][18][19] . En cambio, Ravaioli et al 20 observaron cĂłmo la obtenciĂłn de necrosis parcial tras la TACE era una variable predictora de recurrencia tumoral tras el TH.…”
Section: Discussionunclassified
“…[2][3][4][5] However, other studies have found no impact on this endpoint. 6,7 Despite early promising results from well-designed single center studies, [8][9][10] no study has proven that neoadjuvant TACE improves post transplant disease-free survivals. [11][12][13][14][15] The variability in response rates to TACE suggest that there are multiple factors which influence outcome after this treatment.…”
Section: Introductionmentioning
confidence: 95%